2015
DOI: 10.1007/s11606-015-3381-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Physician-Only and Physician–Patient Intervention on Colorectal Cancer Screening Discussions Between Providers and African American and Latino Patients

Abstract: BACKGROUND: Physician recommendation of colorectal cancer (CRC) screening is a critical facilitator of screening completion. Providing patients a choice of screening options may increase CRC screening completion, particularly among racial and ethnic minorities. OBJECTIVE: Our purpose was to assess the effectiveness of physician-only and physician-patient interventions on increasing rates of CRC screening discussions as compared to usual care. DESIGN: This study was quasi-experimental. Clinics were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…3033 However, no prior studies were found that have demonstrated that a CRC screening decision aid or educational video meaningfully increases discussion of more than one screening test option (a proxy for shared decision making). 34 Further, although a few CRC decision aid studies have enrolled diverse, vulnerable patient populations, 33,35 there is a need to identify screening interventions that are effective in Latino populations, who have substantially lower screening rates than the general U.S. population. 36 However, no U.S. clinical trials of CRC screening decision aids conducted in Spanish-speaking populations were found.…”
Section: Introductionmentioning
confidence: 99%
“…3033 However, no prior studies were found that have demonstrated that a CRC screening decision aid or educational video meaningfully increases discussion of more than one screening test option (a proxy for shared decision making). 34 Further, although a few CRC decision aid studies have enrolled diverse, vulnerable patient populations, 33,35 there is a need to identify screening interventions that are effective in Latino populations, who have substantially lower screening rates than the general U.S. population. 36 However, no U.S. clinical trials of CRC screening decision aids conducted in Spanish-speaking populations were found.…”
Section: Introductionmentioning
confidence: 99%
“…Budget constraints and time pressures were also reported as barriers to longer training; it is unrealistic for busy clinicians to attend even a 1-day training [7,15,46] . In the remaining articles, four add-on session types were identified: supervision n = 5 [3, 4*, 8*, 37*, 44*] , coaching n = 4 [27, 28*, 40*, 48*] , booster n = 2 [18,31] and telephone calls n = 3 [5*, 11, 31] . 4.…”
mentioning
confidence: 99%
“…Three articles offered no information on role-play [18,24,25] , but all others mentioned using role-play as an experiential learning technique either with n = 33 [1, 2, 6, 8*, 9-16, 19*, 20*, 21-23, 26*, 27, 29, 30, 32-34, 36, 38, 39, 40*, 41, 42, 43*, 48*, 49] or without n = 13 [3, 4*, 5*, 7, 17, 28*, 31, 35*, 37*, 44*, 45-47] specified feedback from facilitators, other participants and/or simulated patients. Three articles offered no information on role-play [18,24,25] , but all others mentioned using role-play as an experiential learning technique either with n = 33 [1, 2, 6, 8*, 9-16, 19*, 20*, 21-23, 26*, 27, 29, 30, 32-34, 36, 38, 39, 40*, 41, 42, 43*, 48*, 49] or without n = 13 [3, 4*, 5*, 7, 17, 28*, 31, 35*, 37*, 44*, 45-47] specified feedback from facilitators, other participants and/or simulated patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The 'waiting room video' is an attractive way to use patient downtime before an appointment, and is available in both English and Spanish. Providing information directly to patients matches the intent of the Ecological Model for Ambulatory Patient Safety in Chronic Disease to produce collaboration between an activated patient and a proactive practice team.…”
mentioning
confidence: 99%